TEACHING UZBEKISTAN’S MUSICAL HERITAGE THROUGH NATIONAL INSTRUMENTS: MODERN METHODOLOGICAL APPROACHES - Khurshida Sattorova (Bright Mind Publishing, 2025)
This article examines methodological approaches to transmitting Uzbekistan’s musical heritage to younger generations through the use of national musical instruments within modern educational settings. The study explores the educational, aesthetic, and cultural significance of traditional Uzbek instruments, highlighting ways to enhance instructional effectiveness through interactive methods, digital technologies, and integrative pedagogical strategies. A combination of literature analysis, pedagogical observation, interviews, and experimental–practical methods was employed in the research. The findings demonstrate that integrating contemporary pedagogical technologies with traditional instrumental instruction contributes significantly to strengthening young people’s national identity and fostering a deeper appreciation of cultural heritage.
Keywords: Uzbek national musical instruments, musical heritage, modern methodology, national values, interactive methods, aesthetic education, music instruction, digital technologies, competence.